Adolescents’ Knowledge, Attitudes, and Non-Pharmacology Practice of Treating Dysmenorrhea - Latifah, Lutfatul; Darajati, Nabila Mentari; Kartikasari, Aprilia (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Background: Dysmenorrhea is a disorder of abdominal pain often experienced by adolescents during menstruation. This often interferes with daily activities, so it requires effective treatment, including non-pharmacology techniques. However, many adolescents still do not know how to treat dysmenorrhea. Aim: This study aims to determine the relationship between the knowledge and attitudes of adolescents toward non-pharmacology practices for treating dysmenorrhea. Method: The method used in this research are quantitative with a cross-sectional design. The sampling technique used consecutive sampling with a total sample of 106 respondents. Test analysis in this research using the Chi-Square test. Results: The result showed that knowledge in the medium category with 52 people (14.2%), attitude in the negative category with 59 people (55.7%), and adolescents do not handle practice with 81 people (76.4%). The results of the Chi-Square test between variables showed the adolescents’ knowledge with a p-value = 0.230 (p > 0.05) and adolescents’ attitudes with a p-value = 0.390 (p > 0. 05) towards non-pharmacology practices in treating dysmenorrhea. Conclusion: There is no relationship between adolescents’ knowledge and attitudes with the non-pharmacology practice of treating dysmenorrhea.